College of Agriculture 2019 Annual Report - Minton, Ernest J. (My University, 2019)
This informal report to the Kansas Legislature summarizes the impact of Kansas State's College of Agriculture educational programs in 2019.
UNN34A_2019_01
Keywords: UNN34A; Administrative and Research Reports; legislature